The effects of market-based reforms on access to electricity in developing countries: a systematic review - Gunther Bensch (Journal of Development Effectiveness, 2019)
Market-based reforms have been promoted over the past decades to improve the performance of the power sector. This systematic review assesses the effect of market-based reforms in developing countries on intermediate outcomes like technical efficiency and the resulting impacts on electricity access. Using a pool of 70 well-designed qualitative and quantitative studies, the review synthesizes impacts of private sector involvement, privatisation, liberalisation, and regulation. This mixed-methods approach detects only few and mostly weak effect patterns for reform types sufficiently evaluated in the primary literature. The qualitative synthesis further distils factors that likely contribute to successful electricity sector reforms as tentative guidance for coherent policy delivery.
Keywords: 330; Energy; electric utilities; reform; efficiency; developing countries